Social Entrepreneurship as a Form of Social Mandate and Implications for Today`s Evangelism - Gabriel Dhandi; Sutrisno Sutrisno (Sekolah Tinggi Teologi Moriah, 2022)
All believers are appointed by God to do His work on earth. There are three imperatives or orders: the cultural imperative, the missionary imperative, and the social imperative. Every believer has a duty to fulfill this commission, a responsibility that must be fulfilled. Nevertheless, some believers do not feel responsible for fulfilling their social and divine mission. A social commission is a divine command given to believers to pay attention and care for social problems as they arise. However, some believers still ignore social imperatives on the grounds that human social conditions will surely be destroyed and destroyed, so there is no point in influencing the structure of society. A Christian's only duty is to perform only spiritual acts of salvation. Indeed, when this social task is carried out by believers, there is a great opportunity if this task is carried out correctly and properly. However, if we consider social missions further, we find that social entrepreneurship is a social mission. Social entrepreneurship can also be a vehicle for gospel preaching today. The method of answering this research question is presented in a narrative format using a qualitative writing method and then a literature review approach. Using this method, we can understand that even though social entrepreneurship is a form of social mission, it can be realized through social entrepreneurship. Social entrepreneurship can not only help people with social problems, but it can bring God's universal love to those who do not know God. Also, Allah's Shalom is readily available to all mankind from all aspects of life.